Variations in phase and amplitude of rhythmic clock gene expression across prefrontal cortex, hippocampus, amygdala, and hypothalamic paraventricular and suprachiasmatic nuclei of male and female rats. - Chun, Lauren E. (J Biol Rhythms, 2015)
The molecular circadian clock is a self-regulating transcription/translation cycle of positive (Bmal1, Clock/Npas2) and negative (Per1,2,3, Cry1,2) regulatory components. While the molecular clock has been well-characterized in the body’s master circadian pacemaker, the hypothalamic suprachiasmatic nucleus (SCN), only a few studies have examined both the positive and negative clock components in extra-SCN brain tissue. Furthermore, there has yet to be a direct comparison of male and female clock gene expression in the brain. This comparison is warranted, as there are sex differences in circadian functioning and disorders associated with disrupted clock gene expression. This study examined basal clock gene expression (Per1, Per2, Bmal1 mRNA) in the SCN, prefrontal cortex (PFC), rostral agranular insula, hypothalamic paraventricular nucleus (PVN), amygdala, and hippocampus of male and female rats at 4-h intervals throughout a 12:12h light:dark cycle. There was a significant rhythm of Per1, Per2, and Bmal1 in the SCN, PFC, insula, PVN, subregions of the hippocampus, and amygdala with a 24-h period, suggesting the importance of an oscillating molecular clock in extra-SCN brain regions. There were three distinct clock gene expression profiles across the brain regions, indicative of diversity amongst brain clocks. Although generally the clock gene expression profiles were similar between male and female rats, there were some sex differences in the robustness of clock gene expression (e.g., females had less robust rhythms in the medial PFC, more robust rhythms in the hippocampus, and a greater mesor in the medial amygdala). Furthermore, females with a regular estrous cycle had attenuated aggregate rhythms in clock gene expression in the PFC compared to non-cycling females. This suggests that gonadal hormones may modulate the expression of the molecular clock.